The second fat graft has significantly better outcome than the first fat graft for Romberg syndrome: A study of three-dimensional volumetric analysis. Issue 12 (December 2016) - Jiang, Taoran; Xie, Yun; Zhu, Ming; Zhao, Peijuan; Chen, Zhuxin; Cheng, Chen; Huang, Rulin; Liu, Kai; Li, Qingfeng
Summary: Background: Patients with congenital or acquired deformities always need fat graft at least twice to remodel facial contour. The purpose of this study was to objectively evaluate the outcomes of the first and second fat grafts for Romberg syndrome by using three-dimensional (3D) volumetric analysis. Method: A retrospective study was conducted using the medical records of 13 patients with Romberg disease who were treated with fat graft twice for facial filling. Patient and surgeon satisfactions were evaluated by comparing the preoperative and postoperative two-dimensional (2D) photographs. The preoperative and postoperative 3D images were analyzed with professional analysis software to calculate the volume discrepancy between them. Result: According to the 2D photographs, both patients and the surgeon were more satisfied with the cosmetic results of the second fat graft. There was no significant statistical difference in the injection volumes between the two surgeries (p = 0.1); however, the survival rate of the second fat graft (75.1% ± 7.7%) was much higher than that of the first (43.3% ± 11.1%) with a significant difference (p < 0.01). Conclusion: In this study, 3D images were used to objectively evaluate the survival rate of fat graft. The results showed that the second fat graft without any sophisticated procedures could acquire better cosmetic result and volume retention in Romberg syndrome. This study result could serve as a guide for clinical surgeons to forecast the outcome of sequential fat graft for patients with congenital or acquired deformities.